Pengaruh Lingkungan Kerja, Kompensasi Dan Kepemimpinan Terhadap Efektivitas Kerja Pegawai - Rina Wulandari; Syarifuddin Syarifuddin (Jurnal Manajemen, 2022)
The purpose of this study was to determine the variables that affect work effectiveness in office employees of Pota Sambi Rampas District, East Manggarai Regency through interview techniques. These variables include: Work Environment, Compensation and Leadership. The type of data used in this study was primary data and secondary data obtained directly from the study subjects, namely office employees of Sambi Rampas District, East Manggarai Regency with a population of 30 people. In this case the researcher used the entire population number as a sample by the census method. The data analysis method used to answer the research objectives is multiple linear regression analysis. Hypothesis testing is carried out by fulfilling the classical assumption test first to ensure that the research model is feasible to use which is then continued by using a partial test (T test), simultaneous test (F test), and determination coefficient test (RÂ²) with a significant level of (a) 5%. Based on the results of data analysis, partially (Test T) the Work Environment variable has a positive and significant effect on Employee Work Effectiveness with a table t value of 2.05553, acalculated t value of 4.755 and a significance value of 0.000. The Compensation Variable has a positive and significant effect on Employee Work Effectiveness with a table t value of 2.05553, acalculated t value of 2.267 and a significance value of 0.032. The Leadership Variable has a positive and significant effect on Employee Work Effectiveness with a table t value of 2.05553,a calculated t value of 2.126 and a significance value of 0.043. Simultaneously (Test F) the variables Work Environment, Compensation and Leadership have a positive and significant effect on Employee Work Effectiveness witha calculated F value of 29.277 > Ftable 2.98 and a significance value of 0.000. The RÂ² value is 0.772 so that the variables of Work Environment, Compensation and Leadership are able to influence the employee work effectiveness variable by 77.20% and the remaining 22.80% is influenced by other factors outside of this study.